Biotransformation of acetoin to 2,3-butanediol: Assessment of plant and microbial biocatalysts - Javidnia, Katayoun (Res Pharm Sci, 2016)
2,3-Butanediol (2,3-BD) is a valuable bulk chemical owing to its extensive application in chemical and pharmaceutical industry with diverse applications in drug, cosmetics and food products. In the present study, the biotransformation of acetoin to 2,3-BD by five plant species (Brassica oleracea, Brassica rapa, Daucuscarota, Pastinaca sativa, and Raphnussativus) and five microorganisms (Aspergillusfoetidus, Penicillumcitrinum, Saccharomyces carlbergensis, Pichiafermentans, and Rhodotrulaglutinis) was investigated as a method for the production of 2,3-BD, which can serve as an alternative to the common pentoses and hexoses fermentation by microorganisms. The produced 2,3-BD stereoisomers were characterized and their total conversion yields were determined. The results showed that the examined plants can be used as a green factory for the production of all 2,3-BD stereoisomers, except B. rapa. In microorganisms, P. fermentans and S. carlbergensis produced (–)-2R,3R and mesobutanediol, while P. citrinum produced (+)-2S,3S and mesobutanediol. R. glutinis and A. foetidus produced all three isomers. In conclusion, efficient whole-cell biocatalysts from plants and microorganisms were determined in the bioconversion of acetoin to 2,3-BD. The profile of produced stereoisomers demonstrated that microorganisms produce more specific stereoisomers.